Analisis Pengendalian Biaya Konstruksi Dengan Metode Life Cycle Cost (LCC) pada jembatan - Franata, Hengky; Honesti, Leli; Nandikk, Misbah (Universitas Andalas, 2025)
The development of transportation infrastructure in the form of roads and bridges is one of the elements that support the connectivity and economic growth of a community or a country. Bridges not only function to facilitate goods and people, but also as infrastructure that connects areas separated by natural barriers, such as rivers, valleys, ravines, railways and so on. So it is important to integrate methods that can provide a complete picture of the total costs incurred during the bridge's design life including the cost of maintenance and replacement of components that are no longer functioning or damaged. The purpose of this study is to determine the total life cycle cost of the Andalas University bridge project. Using the Life Cycle Cost (LCC) method by calculating the future value (Future present) during the 100-year design life. The results of this study are in the form of a Cash Flow Diagram that explains the costs of expenditure and income that occur during the 100-year design life of the bridge. So it can be concluded that the total life cycle cost of the Andalas University bridge is Rp. 11,948,862,990.36 which includes the initial cost of Rp. 8,999,998,475.33 or 72.32%, the operational costs during the design life are Rp2,088,775,264.28 or 17.48%, the bridge structural costs are Rp125,210,632.80 or 1.05%, and the bridge mechanical costs are Rp734,878,617.96 or 6.15%. Therefore, applying the life cycle cost (LCC) method can provide a more accurate picture of bridge planning finances and improve cost management efficiency by considering periodic maintenance and operational costs.